PERSEPSI MAHASISWA TERHADAP KOMUNIKASI ANTARPRIBADI DOSEN PEMBIMBING SKRIPSI DALAM PROSES BIMBINGAN SKRIPSI - Lussy Dwiutami Wahyuni; Fellianti Muzdalifah (Perspektif Ilmu Pendidikan, 2010)
The purpose of this research is to identify students’ perception of the supervisors’ interpersonal communication in guiding the students to complete scientific writing as a requirement to complete their study program at the Department of Psychology, School of Education, State University of Jakarta. As samples, 30 students were selected with incidental technique. The result of the research showed that the students have positive perception of their supervisors’ interpersonal communication. It was stated that the supervisors are fair, empathy, supporting, helpful, having positive attitude and tolerant. No students found problems in communication with the supervisor and fell the supervisors were able to develop a good intrapersonal communication.